Capability Level Analysis of IT Governance Using COBIT 5 on Continuity and Availability Of Services (Case Study: LMS Spada Wimaya) - Dyah Anggraini Kartika Putri; Juwairiah Juwairiah; Frans Richard Kodong (Telematika, 2022)
Purpose: This study aims to assess the capability level to determine the condition of the capability level as-is, to-be, gap analysis and provide recommendations for improving IT governance in the continuity and availability process of LMS Spada Wimaya service. Design/methodology/approach: The capability level assessment refers to the COBIT 5 Process Assessment Model (PAM) assessment criteria with the research stages adopting the COBIT 5 Assessment Process Activities. Findings/result: Based on the urgency and problems that occur in LMS Spada Wimaya related to the continuity of service availability, the appropriate COBIT 5 enterprise goals are chosen, namely Business Service Continuity and Availability which describes in achieving the vision and mission goals of UPN "Veteran" Yogyakarta related to the procurement of LMS Spada Wimaya. The process of mapping results is prioritized based on impact and importance. The results of the assessment of the current capability level (as-is) in the BAI06, DSS03, DSS05, and MEA01 processes are at level 2 with the expected target capability level (to-be) at level 3 with a gap level of 1. DSS01, DSS02, and DSS04 are at level 1 with a target capability level (to-be) expected at level 3 with a gap level of 2. output criteria, setting performance goals and targets, making Standard Operating Procedures (SOP), conducting performance assessments to ensure compliance. Originality/value/state of the art: This study has the same focus as previous research, which is measuring the ability of the IT governance level with the criteria for the COBIT 5 Model Assessment Criteria (PAM), but is implemented in a different case study and the focus of the process is in accordance with the results of mapping the alignment of organizational goals with COBIT 5 IT goals according to urgency and problems that describe in achieving the vision and mission of the object of research.